The Trade War Of China And The Us In 2021, And It’s Impact On The Indonesian Economy - Napang, Marthen; Rohman, Syaiful (UI Scholars Hub, 2022)
This study will explore the trade war between China and the United States (US). The US government initially paid close attention to the principle of free and open economics; this was because the US believed that free trade was not only to develop the US domestic economy but also as a tool to generate mutual benefits between cooperating countries. This is in contrast to the US in President Donald Trump 2017-2021, which implemented a policy of protectionism against Chinese trade. Trump did this as a strategy to overcome the negative impact of free trade, which in the end, the US trade dominance was rivaled by China's economic progress. In the era of President Joe Biden, the policy did not change even though the public demanded renegotiation. In this study, the author uses the theory of free trade and economic nationalization. The author uses exploratory qualitative research methods. The study results show that the protectionism policy is part of the US's disappointment with the free trade system because it is not in accordance with the wishes of the US. Without realizing it, the policy of protectionism has become a boomerang for the US domestic economy, considering that free trade is aimed at mutual benefit. This has an impact on the Chinese economy and the Indonesian economy as a developing country. Therefore, protectionism does not benefit the US, considering that the US cannot get the maximum benefit.